Study of the Curing Kinetics toward Development of Fast-Curing Epoxy Resins. Issue 2 (22nd January 2017) - Lakho, Dildar Ali; Yao, Donggang; Cho, Kyonghoon; Ishaq, Muhammad; Wang, Youjiang
ABSTRACT: Rapid resin transfer molding is suitable for high-volume production of composite products. In this work, the epoxy systems with long pot life, i.e., with low reactivity at room temperature and low viscosity for fast injection into the mold cavity and reinforcing fabric, were developed by varying different concentrations of diluent and catalyst. Once infusion is completed, such epoxy formulations were capable of reacting fast at cure temperatures. Different formulations were developed to achieve such goals. This paper reports on the investigation of cure rate, cure temperature, cure time, glass transition temperature, and in situ cure monitoring using differential scanning calorimetry. GRAPHICAL ABSTRACT: